Mycobacterium tuberculosis Infection Induces HDAC1-Mediated Suppression of IL-12B Gene Expression in Macrophages - Chandran, Aneesh; Antony, Cecil; Jose, Leny; Mundayoor, Sathish; Natarajan, Krishnamurthy; Kumar, R. Ajay (Frontiers in Cellular and Infection Microbiology, 2015)
Downregulation of host gene expression is one of the many strategies employed by intracellular pathogens such as Mycobacterium tuberculosis (MTB) to survive inside the macrophages and cause disease. The underlying molecular mechanism behind the downregulation of host defense gene expression is largely unknown. In this study we explored the role of histone deacetylation in macrophages in response to infection by virulent MTB H37Rv in manipulating host gene expression. We show a significant increase in the levels of HDAC1 with a concomitant and marked reduction in the levels of histone H3-acetylation in macrophages containing live, but not killed, virulent MTB. Additionally, we show that HDAC1 is recruited to the promoter of IL-12B in macrophages infected with live, virulent MTB, and the subsequent hypoacetylation of histone H3 suppresses the expression of this gene which plays a key role in initiating Th1 responses. By inhibiting immunologically relevant kinases, and by knockdown of crucial transcriptional regulators, we demonstrate that protein kinase-A, CREB and c-Jun play an important role in regulating HDAC1 level in live MTB-infected macrophages. By chromatin immunoprecipitation analysis, we prove that HDAC1 expression is positively regulated by the recruitment of c-Jun to its promoter. Knockdown of HDAC1 in macrophages significantly reduced the survival of intracellular MTB. These observations indicate a novel HDAC1-mediated epigenetic modification induced by live, virulent MTB to subvert the immune system to survive and replicate in the host.